Knowledge Transfer via Pre-training for Recommendation: A Review and Prospect - Zeng, Zheni; Xiao, Chaojun; Yao, Yuan; Xie, Ruobing; Liu, Zhiyuan; Lin, Fen; Lin, Leyu; Sun, Maosong (Frontiers in Big Data, 2021)
Recommender systems aim to provide item recommendations for users and are usually faced with data sparsity problems (e.g., cold start) in real-world scenarios. Recently pre-trained models have shown their effectiveness in knowledge transfer between domains and tasks, which can potentially alleviate the data sparsity problem in recommender systems. In this survey, we first provide a review of recommender systems with pre-training. In addition, we show the benefits of pre-training to recommender systems through experiments. Finally, we discuss several promising directions for future research of recommender systems with pre-training. The source code of our experiments will be available to facilitate future research.